Coherent matrix of plasmonic beams - Novitsky, Andrey; Lavrinenko, Andrei V. (Photonics Letters of Poland, 2013)
We consider monochromatic electromagnetic beams of surface plasmon-polaritons created at interfaces between dielectric media and metals. We theoretically study non-coherent superpositions of elementary surface waves and discuss their spectral degree of polarization, Stokes parameters, and the form of the spectral coherence matrix. We compare the polarization properties of the surface plasmons-polaritons as three-dimensional and two-dimensional fields concluding that the latter is superior. Full Text: PDF References G.A. Siviloglou J. Broky, A. Dogariu, D.N. Christodoulides, "Observation of Accelerating Airy Beams", Phys. Rev. Lett. 99, 213901 (2007). CrossRef G.A. Siviloglou, D. N. Christodoulides, "Accelerating finite energy Airy beams", Opt. Lett. 32, 979 (2007). CrossRef J. Durnin, "Exact solutions for nondiffracting beams. I. The scalar theory", JOSA A 4, 651 (1987). CrossRef A. April, "Bessel?Gauss beams as rigorous solutions of the Helmholtz equation", JOSA A 28, 2100 (2011). CrossRef E. Wolf, "Optics in terms of observable quantities", Nuovo Cimento 12, 884 (1954a). CrossRef T. Setala, A. Shevchenko, M. Kaivola, A.T. Friberg, "Degree of polarization for optical near fields", Phys. Rev. E 66, 016615 (2002). CrossRef J. Ellis, A. Dogariu, S. Ponomarenko, E.Wolf, "Degree of polarization of statistically stationary electromagnetic fields", Opt. Commun. 248, 333 (2005). CrossRef C. Brosseau, A. Dogariu, "Chapter 4 Symmetry properties and polarization descriptors for an arbitrary electromagnetic wavefield", Progress in Optics 49, 315 (2006). CrossRef A. Norrman, T. Setala, A.T. Friberg, "Partial spatial coherence and polarization properties of surface plasmon fields", Proc. of SPIE, 8011, 80113O (2011). CrossRef R. Carminati, J.-J. Greffet, "Near-Field Effects in Spatial Coherence of Thermal Sources", Phys. Rev. Lett., 82, 1660 (1999). CrossRef C.J. Zapata-Rodrigues, S. Vukovic, M.R. Belic, D. Pastor, J.J. Miret, "Nondiffracting Bessel plasmons", Opt. Express, 19, 19572 (2011). CrossRef A. Minovich, A.E. Klein, N. Janunts, T. Pertsch, D.N. Neshev, Y.S. Kivshar, "Generation and Near-Field Imaging of Airy Surface Plasmons", Phys. Rev. Lett. 107, 116802 (2011). CrossRef F.I. Fedorov, Zh. Prikl. Spectrosk. 2, 523 (1965). F.I. Fedorov, Theory of Gyrotropy (Minsk, Nauka i Technika 1976). A.V. Lavrinenko, I.I. Gancheryonok, T. Dreier, "Theory of optically heterodyned polarization (vectorial) interferometry on the basis of Fedorov’s covariant approach", J. Opt. B: Quantum Semiclass. Opt. 3, S202 (2001). CrossRef S.A. Maier, Plasmonics: Fundamentals and Applications (Berlin, Springer, 2007). A.V. Novitsky and L.M. Barkovsky, "Operator matrices for describing guiding propagation in circular bianisotropic fibres", J. Phys. A: Math. Gen. 38, 391 (2005). CrossRef